2011
DOI: 10.1002/cbic.201100130
|View full text |Cite
|
Sign up to set email alerts
|

C5‐DNA Methyltransferase Inhibitors: From Screening to Effects on Zebrafish Embryo Development

Abstract: DNA methylation is involved in the regulation of gene expression and plays an important role in normal developmental processes and diseases, such as cancer. DNA methyltransferases are the enzymes responsible for DNA methylation on the position 5 of cytidine in a CpG context. In order to identify and characterize novel inhibitors of these enzymes, we developed a fluorescence-based throughput screening by using a short DNA duplex immobilized on 96-well plates. We have screened 114 flavones and flavanones for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 46 publications
1
85
0
1
Order By: Relevance
“…The K m,DNA values reported for full-length Dnmt3a are 2.5 M for 30-mer duplex non-methylated and hemi-methylated DNAs (34), 2.7 M for poly(dIdC), and 3.5 M for poly(dGdC) (35). All of these reported values are more than 10-fold larger than the DNA concentration used in the IC 50 experiment. Yet, as can been seen in Fig.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…The K m,DNA values reported for full-length Dnmt3a are 2.5 M for 30-mer duplex non-methylated and hemi-methylated DNAs (34), 2.7 M for poly(dIdC), and 3.5 M for poly(dGdC) (35). All of these reported values are more than 10-fold larger than the DNA concentration used in the IC 50 experiment. Yet, as can been seen in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…5B). The higher IC 50 for LCA inhibition of Dnmt1 (351-1600) than for Dnmt1 (621-1600) can be explained in two ways. First, the RFTS domain-containing enzyme must be assayed at a 10-fold higher concentration of DNA substrate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, SGI-1027 belongs to a family of minor groove DNA binders developed by Denny and collaborators (Datta et al, 2009) and has been shown to inhibit DNA methylation in enzymatic tests and in cancer cells. We developed two families of DNMT inhibitors: procainamide conjugates that are selective of DNA methyltransferases versus histone methyltransferases and flavanoid derivatives that also inhibit DNA methylation in an in vivo model of zebrafish development (Ceccaldi et al, 2011). Since the small molecules identified so far showed less anti-cancer activities than nucleoside analogs and present limited therapeutic interest, we and others have developed high-throughput screening and drug design strategies to discover new inhibitors (Ceccaldi et al, 2013;Kilgore et al, 2013;Weng et al, 2014).…”
Section: Non-nucleoside Inhibitors For Dnmt Selectivitymentioning
confidence: 99%